There's Always Work at the Post Office : African American Postal Workers and the Fight for Jobs, Justice, and Equality - Rubio, Philip F. (Book collections on Project MUSE., 2010)
Rubio, a former postal worker, brings to life the important but neglected story of African American postal workers and the critical role they played in the U.S. labor and black freedom movements. Having fought their way into postal positions and unions, black postal workers--often college-educated military veterans--became a critical force for social change. Centered on New York City and Washington, D.C., the book chronicles a struggle of national significance through its examination of the post office, a workplace with facilities and unions serving every city and town in the U.S.